Complete genetic characterization of carbapenem-resistant Acinetobacter johnsonii, co-producing NDM-1, OXA-58, and PER-1 in a patient source - Tian, Chongmei; Song, Jianqin; Ren, Lingzhi; Huang, Delian; Wang, Siwei; Fu, Liping; Zhao, Yaping; Bai, Yongfeng; Fan, Xueyu; Ma, Tianhong; Ying, Junjie (Frontiers in Cellular and Infection Microbiology, 2023)
The emergence of carbapenemase-producing Acinetobacter spp. has been widely reported and become a global threat. However, carbapenem-resistant A. johnsonii strains are relatively rare and without comprehensive genetic structure analysis, especially for isolates collected from human specimen. Here, one A. johnsonii AYTCM strain, co-producing NDM-1, OXA-58, and PER-1 enzymes, was isolated from sputum in China in 2018. Antimicrobial susceptibility testing showed that it was resistant to meropenem, imipenem, ceftazidime, ciprofloxacin, and cefoperazone/sulbactam. Whole-genome sequencing and bioinformatic analysis revealed that it possessed 11 plasmids. blaOXA-58 and blaPER-1 genes were located in the pAYTCM-1 plasmid. Especially, a complex class 1 integron consisted of a 5′ conserved segment (5′ CS) and 3′ CS, which was found to carry sul1, arr-3, qnrVC6, and blaPER-1 cassettes. Moreover, the blaNDM-1 gene was located in 41,087 conjugative plasmids and was quite stable even after 70 passages under antibiotics-free conditions. In addition, six prophage regions were identified. Tracking of closely related plasmids in the public database showed that pAYTCM-1 was similar to pXBB1-9, pOXA23_010062, pOXA58_010030, and pAcsw19-2 plasmids, which were collected from the strains of sewage in China. Concerning the pAYTCM-3 plasmids, results showed that strains were collected from different sources and their hosts were isolated from various countries, such as China, USA, Japan, Brazil, and Mexico, suggesting that a wide spread occurred all over the world. In conclusion, early surveillance is warranted to avoid the extensive spread of this high-risk clone in the healthcare setting.